The Responsibility of Indonesia for Deforestation Based On United Nations Convention On Biological Diversity - Christina Nitha Setyaningati; Asilah As; Cecealia Zefania Tandiono; Elvira Anastasia Cempaka; Muhammad Rizki (Universitas Ahmad Dahlan, 2019)
Introduction to The Problem: Indonesia is one of the participants of the United Nations Convention On Biological Diversity Or better known as UNCBD. Indonesia has also ratified this UNCBD into Act No. 5 of 1994 on the Ratification of the UNCBD. By this ratification, Indonesia has obligations and responsibilities that must be carried out under the provisions of the Convention. One is about the protection of the environment; in this case, is deforestation relating to biodiversity. Based on UNCBD, Indonesia also should make the implementing Law for the ratification. The problem is that Indonesia has no implementing regulation yet for the ratification.Purpose/Objective Study: The purpose of this paper is to find out the concept of environmental protection; in this case, deforestation based on the UNCBD and positive law in Indonesia. It also suggests what forms of Indonesia’s responsibility and what implementation steps to overcome the deforestation occurring in Indonesia.Design/Methodology/Approach: The research employs the qualitative method based on a normative juridical study. Additionally, the authors used two approaches, which are conceptual and the statute approach.Findings: Indonesia has not explicitly made an implementing law for Act No. 5 of 1994 as a ratification law of UNCBD. For that reason, it is the government responsible for making the implementing regulation. The Indonesian government should pay attention to the previous legal-made experience regarding the other ratification before UNCBD. The simple steps, but the main base reasons are using consideration phrase of the inexistence of implementing regulation for the ratified-UNCBD and also the government responsibility to oblige the ratification.